Cloning useful recombinant cDNA/ mRNA constructs to study cell cycle and Hippo-signalling in preimplantation mouse embryos - Moser, Fabian (Jihočeská univerzita, 2020)
The aim of this thesis was the generation of an in vitro transcription (IVT) plasmid vector containing a cDNA insert for an EGFP Tubulin 6 fusion protein, studying the effect of non phosphorylatable YAP1(S112A) on preimplantation mouse embryo blastomere localisation and generation of Securin GFP mRNA for microinjection in early mouse embryo blastomeres.
Cloning useful recombinant cDNA/ mRNA constructs to study cell cycle and Hippo-signalling in preimplantation mouse embryos